FEATURES OF THE USE OF MATERIALS AND COATINGS FOR THE EFFICIENT WORK OF EQUIPMENT IN THE MINING INDUSTRY - Панчук, Мирослав; Панчук, Андрій; Матвієнків, Олег; Киштопа, Святослав; Мартинюк, Ростислав (SWorldJournal, 2026)
The article analyses the effectiveness of using materials and coatings for technological processes in the mining industry. The use of engineering materials such as polymers, metals and ceramic coatings is appropriate for various niche situations. It has